ANALISIS KESESUAIAN RENCANA KELOLA BLOK PEMANFAATAN HUTAN LINDUNG DI WILAYAH KPH TEPO ASA AROA (KPHL UNIT XIII) PROVINSI SULAWESI TENGAH - Nasanah Lamaligi, Michael Eras; Akhbar, Akhbar; Arianingsih, Ida; Hamka, Hamka (Jurnal Warta Rimba, 2021)
This research was conducted in the protected forest area of the Tepo Asa Aroa Forest Management Unit (KPHL Unit XIII). This research was carried out by maximally comparing planning documents with actual conditions in the field, with the formulation of existing problems, namely to see whether the management plan is based on the criteria for protected forest utilization. which is in the regulation of the director general of forestry planology P.5/VII-WP3H/2012 is in accordance with the implementation in the field. Based on the results of research collected in the field and related agencies, explained that the protected forest utilization block located in the Protection Forest Management Unit (KPHL) Tepo Asa Aroa has the highest area in 94 management plots, and there is the potential for non-timber forest products such as rattan and dammar and environmental services in the form of waterfalls. The suitability of the management plan refers to the criteria, but implementation in the field has not been fully implemented.Keywords : Protection Forest, Planning Management, Forest Management Unit